’n Nuwe vertaling van die Bybel in Afrikaans: ’n teoretiese en praktiese oriëntering - Van der Merwe, CHJ; Basson, CS (Nederduitse Gereformeerde Teologiese Tydskrif, 2003)
The aim of this article is to contribute to the development of a justifiable theoretical model for a new translation of the Bible in Afrikaans. It documents the historical starting point and theoretical reflection that underlies the functionalistic model of Christiane Nord, the practical procedures that were followed to test the practical feasibility of the model, the findings that were made and the implications that it entails for a new translation of the Bible in Afrikaans. It also particularly shows that a theoretical justifiable translation of the Bible, in terms of a functionalistic approach, seems to be one that makes certain demands on the commissioning authority. First, the commissioning authority should be well informed in terms of the needs and “subjective theories” of the intended target language audience. Second, the commissioning authority should be inform the target language audience in detail in terms of the strategies that will be followed to, on the one side, fulfil their needs and, on the other side, to ensure loyalty to the source text.